DIVERSITY OF AMPHIBIANS IN TROPICAL PEATLAND ECOSYSTEM: CASE IN BUFFER VILLAGE AROUND CONSERVATION AREA - Iswandaru, Dian; Hasballah, Bayu Ginanjar; Wulandari, Christine; N., Novriyanti; Pangestu, Pandu Galang; Prasetia, Hendra (Jurnal Belantara, 2025)
Peatlands are vulnerable to fire, causing ecological damage that threatens biodiversity, one of which is amphibians. The nature of amphibians which are sensitive to environmental changes can be used as a bioindicator of the quality of a disturbed environment, including in buffer villages around conservation areas. This research aims to analyze the diversity of amphibians and their relationship with temperature and air humidity. The method used is Visual Encounter Survey (VES) in two types of habitats, namely oil palm plantations and swamps. Data analysis used the Shannon-Wiener species diversity index, the Pielou species evenness index, and the Pearson correlation test. The research results found 6 species of amphibians, namely Hylarana erythraea, Hylarana nicobariensis, Fejervarya limnocharis, Fejervarya cancrivora, Duttaphrynus melanustictus, and Hylarana baramica. The diversity index (H') in oil palm plantations and swamps is H'=1.46 and H'=1.10 in the medium category. This shows that ecologically, the conditions of the habitat types of oil palm plantations and swamps in the buffer villages around the Orang Kayo Hitam Forest Park after land burning can support amphibian life. Key words: Amphibians, conservation area, diversity, tropical peatland.